Effective Dehydration of Fructose Over Stable Ti-Doped SBA-15 Catalysts - Zhu, Yutong; Xu, Xiaofei; He, Jian; Guo, Jie; Song, Ke (Frontiers in Chemistry, 2022)
High-effective synthesis of 5-hydroxymethylfurfural (HMF) from carbohydrates is an interesting reaction among biomass valorization. The as-synthesized Ti-SBA-15 catalysts with mesoporous structures showed high catalytic efficiency for the conversion of fructose to HMF. Ti-SBA-15 catalysts with different Si/Ti ratios were characterized by characterization techniques such as elemental analysis, XRD, TEM, N2 adsorption–desorption, NH3-TPD, and pyridine-FTIR. The acidity of Ti-SBA-15 catalysts could be tuned by altering addition amount of titanium. The effects of reaction conditions, including reaction time, temperature, and amount of catalyst, on the conversions of fructose and the yields of HMF were also investigated. It is found that Ti-SBA-15 catalysts whose Si/Ti ratio is 120 gave the best yields of HMF, which demonstrated 100% conversion of fructose with a maximum HMF yield of 82% at 140°C after 1 h. In addition, its catalytic performance was retained after 5 recycles in fructose conversion reaction, proving its good catalytic stability.